English Spelling Errors Committed by the Blind - Nimatul Lailiyah; Iswahyuni Iswahyuni; Alies Poetri Lintangsari (The Center for Disability Studies and Services Brawijaya University, 2020)
Despite the outgrowing trend on assistive technology assisting blind student to be fully participate in education, the challenges remain in the area of English language learning. The inconsistency of the sound-spelling relationship in English apparently triggers the spelling problems for the Blind student since he tends to encode syllables by as it sounded. This study aims to identify, classify and analyze the spelling errors committed by the blind students in learning English using the classification of NEFR (National Foundation for Educational Research) that comprises the aspects of omissions, substitutions, insertions, transpositions and grapheme substitution. Employing case study design, this research elaborate the spelling error committed by 1 blind EFL learner enrolling an Academic Writing course in English Language Education Program, Faculty of Cultural Studies, Universitas Brawijaya, Indonesia. The findings expose that the blind students tend to frequently do spelling error in the aspect of grapheme substitution followed by omissions, substitutions, and insertion. Some contributive factors that presumably affecting the errors are (1) lack exposure to the formation of the words, (2) inherent of language (silent letter, homophone and borrowing words), (3) different characteristics of L1 and L2, and (4) student's preferences on reading (use screen reader more than braille text). Thus, the exposure toward phonetics symbol and the sound-letter relationship in English should be more disseminated so the blind student is capable of having a correct spelling.